1982
DOI: 10.1159/000198781
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Secretion in Chronic Pancreatitis with Special Reference to Albumin and Lactoferrin

Abstract: Saliva from one parotid gland was collected under citric acid stimulation in three groups consisting of 69 control subjects and two groups consisting of 25 patients with chronic and relapsing chronic pancreatitis. Mixed saliva was collected under mechanical stimulation from 10 patients and 6 control subjects. Flow rates and the contents of bicarbonate, amylase and protein were determined. In a subgroup of patients and controls albumin and lactoferrin were measured. Wide inter- and intraindividual variations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Albumin concentrations in saliva and other mucosal secretions reflect a passive contribution of serum-derived protein, which may be caused by epithelial inflammation. Changes in albumin content of saliva can be used as a diagnostic tool for certain diseases like chronic pancreatitis (Durr et al, 1982) and stomatitis in cancer therapy patients (Izutzu et al, 1981). In the saliva of orally healthy individuals, albumin can be detected in only very small amounts (Henskens et al, 1993).…”
Section: Albuminmentioning
confidence: 99%
“…Albumin concentrations in saliva and other mucosal secretions reflect a passive contribution of serum-derived protein, which may be caused by epithelial inflammation. Changes in albumin content of saliva can be used as a diagnostic tool for certain diseases like chronic pancreatitis (Durr et al, 1982) and stomatitis in cancer therapy patients (Izutzu et al, 1981). In the saliva of orally healthy individuals, albumin can be detected in only very small amounts (Henskens et al, 1993).…”
Section: Albuminmentioning
confidence: 99%
“…LF was analyzed in the duodenum be cause the duodenal content is easier to obtain routinely than pure pancreatic juice, but the duodenal LF may originate from the duode nal wall, pancreas, biliary tract, PMN as well as from gastric and salivary contaminations [3][4][5]. The degree of sensitivity of our immu noassay of LF is the same or higher than that of radioimmunoassay described in the litera ture [12], and about 1,000 times more ele vated than radial immunodiffusion [10,19].…”
Section: Discussionmentioning
confidence: 81%
“…An increase in lactoferrin content in pure pancreatic juice and in the duodenal aspirate has been found in patients affected by chronic pancreatitis [3][4][5]. Although at first some pathogenetic role of this protein in chronic pancreatitis was suggested [6], this hypothesis was later denied; on the other hand, the presence of lactoferrin in the paro tid saliva of patients suffering from chronic pancreatitis and in patients with chronic pa rotiditis suggested that the increase in lacto ferrin in the pancreatic juice should be con sidered secondary to pancreatitis itself [7,8], Recently, it has been hypothesized [9] that increased lactofcrrin levels in the pancreatic juice of patients with chronic pancreatitis might reflect an increased autolytic activity (crinophagia) of the pancreatic cells, with the aim of destroying the excess of the zymogen granules. This increased activity could be due to an enhanced ductal back-pressure.…”
mentioning
confidence: 99%